2006
DOI: 10.1105/tpc.105.038018
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Rauvolfia serpentina Strictosidine Synthase Is a Novel Six-Bladed β-Propeller Fold in Plant Proteins

Abstract: The enzyme strictosidine synthase (STR1) from the Indian medicinal plant Rauvolfia serpentina is of primary importance for the biosynthetic pathway of the indole alkaloid ajmaline. Moreover, STR1 initiates all biosynthetic pathways leading to the entire monoterpenoid indole alkaloid family representing an enormous structural variety of ;2000 compounds in higher plants. The crystal structures of STR1 in complex with its natural substrates tryptamine and secologanin provide structural understanding of the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
165
0
8

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(179 citation statements)
references
References 43 publications
6
165
0
8
Order By: Relevance
“…STR1 is a 6-bladed b-propeller . Ma et al (2006) identified a common repetitive motif in the b-propeller structures related to STR1: three hydrophobic residues, followed by a small residue (Ser, Thr, Val or Gly) and then a hydrophilic residue, frequently Asp or Glu. LAP3 contains this repetitive motif (see supplemental Fig.…”
Section: Lap3 Is Likely Not a Strictosidine Synthasementioning
confidence: 99%
“…STR1 is a 6-bladed b-propeller . Ma et al (2006) identified a common repetitive motif in the b-propeller structures related to STR1: three hydrophobic residues, followed by a small residue (Ser, Thr, Val or Gly) and then a hydrophilic residue, frequently Asp or Glu. LAP3 contains this repetitive motif (see supplemental Fig.…”
Section: Lap3 Is Likely Not a Strictosidine Synthasementioning
confidence: 99%
“…Strictosidine synthase (Rauvolfia serpentina) has been cocrystallized in the presence of both secologanin (PDB code 2FPC) and tryptamine (PDB code 2FPB), 14 and these structures have allowed the first insights into the substrate binding orientation and enzymatic mechanism. Strictosidine synthase, originally isolated from Catharanthus roseus and R. serpentina almost 30 years ago, 15,16 has been the subject of numerous steady-state kinetic analyses (for two examples, see refs 17,18 ).…”
Section: Introductionmentioning
confidence: 99%
“…14 His307 appears to be involved in binding to the glucose moiety of secologanin as evidenced by the crystal structure and the large increase in secologanin K m after mutation. 14 Site-directed mutagenesis of Tyr151 suggests that the ionizable hydroxyl group does not play an important role in catalysis. 14 Site-directed mutagenesis experiments do support the involvement of glutamate residue (Glu309, R. serpentina numbering) in catalysis (900-fold drop in V max for Glu309Ala).…”
Section: Introductionmentioning
confidence: 99%
“…Heterologous expression gave for the first time quantities of highly purified Rauvolfia proteins suitable for systematic crystallization approaches and elucidation of their threedimensional structures. Strictosidine synthase (STR1), the enzyme generating the biogenetic precursor (strictosidine) of the entire monoterpenoid indole alkaloid family, has recently been crystallized and its X-ray structure has been determined, along with those of complexes with its substrates (Ma et al, 2004(Ma et al, , 2006Koepke et al, 2005). This was the first example from the novel STR1 enzyme family for which the three-dimensional structure has been elucidated (Ma et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Strictosidine synthase (STR1), the enzyme generating the biogenetic precursor (strictosidine) of the entire monoterpenoid indole alkaloid family, has recently been crystallized and its X-ray structure has been determined, along with those of complexes with its substrates (Ma et al, 2004(Ma et al, , 2006Koepke et al, 2005). This was the first example from the novel STR1 enzyme family for which the three-dimensional structure has been elucidated (Ma et al, 2006). A further enzyme, vinorine synthase (VS), located in the middle of the biosynthetic pathway to ajmaline, has also recently been structurally investigated in detail .…”
Section: Introductionmentioning
confidence: 99%